Twenty-five years of blood flow restriction training: What we know, what we don`t, and where to next? - Loenneke, J. P.; Hammert, W. B.; Kataoka, R.; Yamada, Y.; Abe, T. (Journal of Sports Sciences, 2025)
Blood flow restriction is a technique that involves inflating a cuff at the proximal portion of the limb with the goal of reducing arterial inflow into the muscle and venous outflow from the muscle. Low-load or low-intensity exercise in combination with blood flow restriction has been consistently shown to augment adaptations over the same/similar exercise without restriction, with changes in muscle size and strength being two of the most commonly measured adaptations. The purpose of this manuscript is to provide an updated narrative review on blood flow restriction. Blood flow restriction`s history, methodology, safety, and efficacy are highlighted. We discuss the effects of blood flow restriction on changes in muscle size and strength, and also review work completed on other variables (e.g. bone, resting blood flow, tendon, pain sensitivity, cognition, orthostatic intolerance). We finish by highlighting six possible areas for future research: 1) identifying mechanisms for growth and strength; 2) sex differences in the effects of blood flow restriction; 3) individual responses to blood flow restriction; 4) influence of pressure versus amount of blood flow restricted; 5) application of blood flow restriction with higher-loads; and 6) what considerations should be made to test the effects of blood flow restriction.